Illocutionary Acts in the Movie “Capture the Flag” - Argangga Khrisnantara, I Gde Yudhi (Humanis; Vol 22 No 3 (2018), 2018)
This study entitled Illocutionary Acts in the Movie “Capture the Flag” is aimed to explain the type and function of illocutionary acts found in the movie and to analyze the context of situation which determines the illocutionary act of the utterance in the movie. The data were taken from the utterances in the movie entitled “Capture The Flag” and it was explained in descriptive qualitative method. The data were collected by watching the movie and reading the movie script, then by noting down the utterances which belong to illocutionary acts. Then, the data were classified into types of illocutionary acts and their function. Afterwards, the context of situation which determines the illocutionary act of the utterances were defined. There were two theories used in conducting this study. The first theory was proposed by Searle (1976) and supported by Yule about the types of illocutionary acts. The theory was used to analyze the types of illocutionary acts and its function. The other theory usedwas proposed by Holmes (2013) about the context of situation. This theory was applied to explain the intended meaning of the utterances. There were five types of illocutionary acts found in the movie, namely Representatives, Directives, Commisives, Expressives, and Declaratives. The functions of each type were boasting, concluding, claiming, affirming, informing, commanding, warning, suggesting, inviting, threatening, offering, apologizing, thanking, blaming and declaring.